Older adults and caregivers in times of the COVID-19 pandemic in the american continent: a health perspective (Boletín Semillero de Investigación en Familia, 2022)
Introduction: the SARS-CoV-2 pandemic has had great consequences for the population, especially for older adults, who are the most vulnerable population group, especially if they are very old and have chronic diseases. Objective: to characterize the scientific publications produced on the care of older adults and caregivers in times of pandemic in the Americas, during the period between January 2020 and the third quarter of 2021. Materials and methods: documentary, bibliometric and data analysis study. integrative review with a quantitative approach. Pilot test results with 50 scientific publications carried out between 2020 and 2021. The choice was made by applying a checklist, which contains 9 items. Results: 50 scientific publications focused on needs and recommendations for older adults and caregivers, as well as political, economic and social challenges, were included. Conclusions: most authors agree that older people make up one of the most vulnerable populations and that social isolation is the main cause of social, neuronal, emotional and physical decay, so quality care must be provided. This is where the participation of caregivers plays an essential role in the care of older adults.
Keywords: caregivers; COVID-19; elderly; health promotion; older person.